Pengembangan Usaha Kuliner Lokal Kapurung Warung Alfhizar di Kota Palopo - Manase, Tekla Galla’; Wulandari, Astria; Ridha, Rasyid; Suhaeb, Firdaus W. (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the business development strategies of local culinary enterprises at Warung Kapurung AlFhizar in Palopo City, South Sulawesi. This eatery is known as one of the successful business actors in developing traditional regional food, namely kapurung, into a culinary product that is popular among the general public. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. Data analysis is conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. Research results show that business development at Alfhizar's stall includes product innovation, improvement of service quality, utilization of social media as a promotional tool, and strengthening of local identity in every aspect of the business. The implementation of these strategies has a positive impact on increasing the number of customers and the image of Palopo's local cuisine. This study emphasizes that the success of traditional culinary business development can be achieved through a combination of local wisdom and modern business strategies